2021
DOI: 10.2176/nmccrj.cr.2020-0367
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intracranial Neuroendocrine Tumor of the Skull Base Complicated with Tension Pneumocephalus after Radiotherapy

Abstract: Neuroendocrine tumors (NETs) are neoplasms that originate from cells of the endocrine and nervous systems, and are commonly found in the gastrointestinal and respiratory tracts. Primary intracranial NETs are extremely rare and have been the focus of only a few studies thus far. Herein, we report the case of a primary intracranial NET of the skull base complicated with tension pneumocephalus after radiotherapy. An 84-year-old woman visited a local hospital for a head injury, and CT revealed a skull base tumor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 7 ) The skull base bone erosion is also reported to be related to postirradiation CSF leakage. 8 ) Reduction in tumor volume by radiotherapy may cause a connection between the paranasal cavities and CSF space in cases of tumors with dural invasion or bone destruction. Stereotactic radiosurgery, especially GKS, is an established treatment option for intrasellar or parasellar tumors, including pituitary adenomas, craniopharyngiomas, and meningiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 ) The skull base bone erosion is also reported to be related to postirradiation CSF leakage. 8 ) Reduction in tumor volume by radiotherapy may cause a connection between the paranasal cavities and CSF space in cases of tumors with dural invasion or bone destruction. Stereotactic radiosurgery, especially GKS, is an established treatment option for intrasellar or parasellar tumors, including pituitary adenomas, craniopharyngiomas, and meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed CSF leakage has been reported as an infrequent complication of various radiotherapy, including stereotactic radiosurgery for the skull base or parasellar tumors. [1][2][3][6][7][8] In many of these cases, TSS is carried out before radiotherapy. Yamada et al reported a case of delayed CSF leakage after CyberKnife radiation for skull base osteosarcoma and mentioned tumor invasion to the dura mater as a risk factor for radiation-induced CSF leakage.…”
Section: Discussionmentioning
confidence: 99%